What influences feeding decisions for HIV-exposed infants in rural Kenya? - Nabwera, H; Jekosgei, J; Muraya, K; Hassan, A; Molyneux, C; Ali, R; Prentice, A; Berkley, J; Mwangome, M (BioMed Central, 2017)
Background Infant feeding in the context of human immunodeficiency virus (HIV) poses unique challenges to mothers and health care workers in balancing perceived risks of HIV transmission and nutritional requirements. We aimed to describe the decision-making processes around infant feeding at a rural HIV clinic in Kenya. Methods We used a qualitative study design. Between March and August 2011, we conducted in-depth interviews (n=9) and focus group discussions (n=10) with purposively selected hospital and community respondents at Kilifi County Hospital, Kenya. These respondents all had experience of infant feeding in the context of HIV. These interviews were informed by prior structured observations of health care worker interactions with carers during infant feeding counselling sessions. Results Overall, women living with HIV found it difficult to adhere to the HIV infant feeding guidance. There were three dominant factors that influenced decision making processes: 1) Exclusive breastfeeding was not the cultural norm, therefore practising it raised questions within the family and community about a mother’s parenting capabilities and HIV status. 2) Women living with HIV lacked autonomy in decision-making on infant feeding due to socio-cultural factors. 3) Non-disclosure of HIV status to close members due to the stigma. Conclusion Infant feeding decision-making by women living with HIV in rural Kenya is constrained by a lack of autonomy, stigma and poverty. There is an urgent need to address these challenges through scaling up psycho-social and gender empowerment strategies for women, and introducing initiatives that promote the integration of HIV infant feeding strategies into other child health services.